2019
DOI: 10.3390/md17050270
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic Effect of Arthrospira (Spirulina) maxima Supplementation and a Systematic Physical Exercise Program in Overweight and Obese Men: A Double-Blind, Randomized, and Crossover Controlled Trial

Abstract: Low-fat diets, lipid-modifying nutraceuticals and a higher level of physical activity are often recommended to reduce dyslipidemia. A double-blind, randomized, crossover, controlled trial was designed to evaluate the independent and synergistic effects of Arthrospira (Spirulina) maxima supplementation (4.5 g·day−1) with or without performing a physical exercise program (PEP: aerobic exercise (3 days·week−1) + high-intensity interval training (2 days·week−1)) on blood lipids and BMI of 52 sedentary men with exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 49 publications
1
14
0
2
Order By: Relevance
“…Five studies were conducted on both genders, four studies on females, two studies on males and one were unknown. Four studies were implemented in Iran (Akbarpour & Ebrahimzadeh, 2019; Sadeghi, Irandoust, & Taheri, 2018; Shariat, Farhangi, & Zeinalian, 2019; Yousefi, Mottaghi, & Saidpour, 2018), two in Poland (Miczke et al, 2016; Szulinska et al, 2017), two in Cameroon (Ngo‐Matip et al, 2014; Winter et al, 2014), one in Burkina Faso (Bationo, Ouédraogo, Kouanda, & Sondo, 2013), one in India (Ramamoorthy & Premakumari, 1996) and two in Mexico (Hernandez‐Lepe et al, 2018; Hernandez‐Lepe et al, 2019). Characteristics of included studies are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were conducted on both genders, four studies on females, two studies on males and one were unknown. Four studies were implemented in Iran (Akbarpour & Ebrahimzadeh, 2019; Sadeghi, Irandoust, & Taheri, 2018; Shariat, Farhangi, & Zeinalian, 2019; Yousefi, Mottaghi, & Saidpour, 2018), two in Poland (Miczke et al, 2016; Szulinska et al, 2017), two in Cameroon (Ngo‐Matip et al, 2014; Winter et al, 2014), one in Burkina Faso (Bationo, Ouédraogo, Kouanda, & Sondo, 2013), one in India (Ramamoorthy & Premakumari, 1996) and two in Mexico (Hernandez‐Lepe et al, 2018; Hernandez‐Lepe et al, 2019). Characteristics of included studies are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of physical activity, spirulina showed a consistent effect on lipid profile. When it was given in association with physical activity, the best outcome was achieved [ 216 ]. A similar study also showed that spirulina in association with physical activity can improve significantly cardiorespiratory fitness more than a single intervention alone [ 217 ].…”
Section: Nutraceuticals In Atherosclerosismentioning
confidence: 99%
“…However, the analysis was limited by the small number of studies included. A successive placebo controlled RCT evaluating the effects of consumption of 4.5 mg/day of spirulina extract in addition to a physical exercise program for six weeks on 45 overweight and obese men did not find any significant changes in anthropometric parameters, whereas it confirmed the lipid lowering effects [132].…”
Section: Spirulinamentioning
confidence: 86%